Penguatan Literasi Keuangan Islami Menuju Financial Freedom pada Mahasiswa Tahfidz Lembaga Tahfidz Ilmu Al-Qur’an (LTIQ) As-Syifa - Koswara, Asep (Welfare : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to strengthen Islamic financial literacy as an effort to achieve financial freedom among tahfidz students of Lembaga Tahfidz Ilmu Al-Qur’an (LTIQ) As-Syifa. The activity is motivated by the limited application of structured financial management systems among students, despite their strong spiritual foundation. The community service was conducted using an educational and participatory approach as part of the Student Executive Board inauguration and Leadership Training Program. The materials delivered covered the concept of financial freedom, basic financial management, income enhancement strategies, and Islamic financial principles. The results indicate that Islamic value-based financial education reinforces the understanding of financial freedom as a form of financial independence achieved through disciplined, halal, and responsible financial systems. Furthermore, this activity highlights the strategic role of Islamic financial literacy in supporting students’ holistic welfare, encompassing economic, mental, and spiritual dimensions. This community service program is expected to serve as a sustainable model for strengthening Islamic financial literacy within Islamic educational institutions.